Gene action and some genetic parameters for grain yield, its components and growth traits of corn in full diallel cross - Farhood AL- Salim, Salih Hadi; Yousif, Dheya P.; Alzrgani, Mahdi S. M.; Abdulrahman, Abbas Lateef (Journal of Scientific Agriculture, 2017)
The objective of this study was to quantify gene action and some genetic parameters for grain yield, its components and other traits of six varietal hybrids and its parents (AM-145 (A), AM-153 (B) and AM-200 (C) obtained from Ministry of Agriculture, Iraq). All hybrids and their parental entries in full diallel cross were tested at Al-Gharraf suburb, 25 Km north of Al-Nasyria City, Iraq during fall 2013 in RCBD with three replications according to Griffing’s fixed model, method for grain yield, its components and other agronomic traits. Gene action, general and specific combining abilities and broad and narrow sense heritability were estimated. Results showed significant differences among entries for almost all traits except ears/plant, and kernels weight. In addition to GCA and SCA significant variances, GCA variances were more important than SCA variances for all traits except ears/plant, which resulting the more importance of the additive genetic effects. SCA variances suggesting the importance the effects of non-additive effects for ears/plant which demonstrating entries could produce prolificacy plants. Additive genetic variances reflect its importance for all traits except female flowering and grain yield/plant. In general, the dominance degree average for all traits except grain yield/plant showed the over dominant effect and the narrow sense heritability ranged between 0.44-0.64 for female flowering and grain yield, respectively. Grain yield/plant ranged between 97.54- 68.44 g for B x A and C x B, respectively. Cytoplasmic heredity revealed its importance studying for all traits and 2GCA/SCA estimates ranged between 1.86 and 35.9 for ears/plant and female flowering, respectively.